ANALISIS PERGESERAN STRUKTUR EKONOMI DAN IDENTIFIKASI SEKTOR POTENSIAL WILAYAH PENGEMBANGAN (Studi Kasus di Kabupaten Bekasi, Provinsi Jawa Barat) - ; Irwansyah, Sonny (Jurnal Social Economic of Agriculture, 2013)
Economic growth had resulted in a shift on economic structure. Structural transformation was a process of economic structure shift from primary to secondary sector, as the case happened in Bekasi District. Structural or economic transformation from traditional to modern in general could be regarded as a shift related to the change of composition and sectoral contribution to the GDP of a region. This structural process could be achieved by paying attention to the sectors that have specialization, competitive and comparative advantages that would become a priority in the economy. The purpose of this research was to analyze the structure and the changing of economic sectors, to identify any potential sectors in each development region of Bekasi District. The research was conducted in Bekasi District, West Java Province. This study used qualitative design with a case study technique. The data gathered was then analyzed using the Location Quotient, Classical Shift Share and Esteban Marquillas Shift Share. The research results showed that in the period of 2004-2010, while the economic structure shift had not yet seen in the development region I, it had already happened in development regions II, III and IV. Based on the combined analysis it was found that the potential economic sectors which had a high competitiveness, had a competitive advantage, able to specialize, as well as having a comparative advantage in each development area of Bekasi District were as follows: for agriculture and transportation sector, the development region I, II and IV had the potential; mining sector was only potential in the region I; industrial sector was only potential in the region II; building development sector could only be found in the development region II and IV, for trade sector, the region IV proved to be potential; financial sector was only potential in development region II. Keywords: Economic Structure Shift, Potential Economic Sector, Location Quotient, Shift Share